FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN PELAPORAN WAJIB PAJAK DOSEN TETAP UNIVERSITAS TARUMANAGARA DI JAKARTA - Sofia Prima Dewi, Keni Keni (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2012)
The purpose of this research is to examine the effect of taxpayer awareness, knowledge and understanding of tax laws, perceptions of the effectiveness of the tax system and the willingness to pay taxes on taxpayer reporting compliance Tarumanagara University lecturer in Jakarta. Data analysis of 104 respondents conducted with the help of PASW Statistics program version 18.00. The results showed that knowledge and understanding of tax laws and the willingness to pay taxes have a significant effect on taxpayer compliance reporting while the taxpayer awareness and perceptions of the effectiveness of the tax system does not have a significant impact on taxpayer compliance reporting.